An Inventory Approach to the Assessment of Main Traditional Landscapes in Sicily (Central Mediterranean Basin) (LANDSCAPE RESEARCH, 2012)
EU policy for the conservation of cultural landscapes is of particular importance for a region such as Sicily (Italy) which is the site of many Mediterranean traditional cultural landscapes as well as new landscapes created by contemporary agriculture. Such variety of landscape, however, is not supported or confirmed by specialised inventories that identify and classify the typical Main Traditional Landscape (MTL). On the basis of these considerations, the objective of the present paper is to draw up a preliminary inventory and present a brief characterisation of MTLs in Sicily, in line with the multidisciplinary experiences and approaches implemented at European and national levels. In defining the typological units, the terminology used to identify Sicilian MTLs was modified by experiences developed on the mainland, with entries such as: bocage/semi-bocage, coltura promiscua, Mediterranean open field, mountain landscape, huerta and terrace landscape. Using different spatialised data layers, including those concerned with the main historical processes of land use and land use change, a total of eight MTLs have been detected, mapped, and concisely described. The distribution and importance of terracing systems within the different MTLs is highlighted as one of the most relevant traditional elements in the rural scenario.
From Duplicate 1 (

Forest types for biodiversity assessment at regional level: the case study of Sicily (Italy) (European Journal of Forest Research, 2007)
Within Europe the question of plant coenosis is attracting growing interest. The quality and quantity of collected information on forest resources at a global level largely depends on the capacity to collect and analyse data at national and sub-national scale in a way compatible with those at global or continental levels. In Italy the acceptance of all the international agreements and protocols on the protection of the environment and management of natural resources, requires a standardization of collected information and statistics, with the aim to produce homogeneous and integrative data at global level. This need is reﬂected in the following points: (1) the adoption of a classiﬁcation system of land use and forest cover compatible with international hierarchical systems and deﬁnitions; (2) the identiﬁcation of standard procedures in data collection and data elaboration. To classify natural resources and, in this case study, forest resources, implies to order natural and semi natural coenosis, forest and pre-forest communities, in a systematic way, according to the applied variables and to the scale detail. The solution proposed in this case study is organised according to forest management, through the adoption of the habitat approach, describing forest and pre-forest types in a synoptic way and performing a system of nomenclature in agreement with the international standards initiatives. In this way, the characterization of forest types at community level is related to the environmental planning for the protection of biodiversity

Forest types for biodiversity assessment at regional level: the case study of Sicily (Italy) - Cullotta, Sebastiano; Marchetti, Marco (European Journal of Forest Research, 2007)
Within Europe the question of plant coenosis is attracting growing interest. The quality and quantity of collected information on forest resources at a global level largely depends on the capacity to collect and analyse data at national and sub-national scale in a way compatible with those at global or continental levels. In Italy the acceptance of all the international agreements and protocols on the protection of the environment and management of natural resources, requires a standardization of collected information and statistics, with the aim to produce homogeneous and integrative data at global level. This need is reﬂected in the following points: (1) the adoption of a classiﬁcation system of land use and forest cover compatible with international hierarchical systems and deﬁnitions; (2) the identiﬁcation of standard procedures in data collection and data elaboration. To classify natural resources and, in this case study, forest resources, implies to order natural and semi natural coenosis, forest and pre-forest communities, in a systematic way, according to the applied variables and to the scale detail. The solution proposed in this case study is organised according to forest management, through the adoption of the habitat approach, describing forest and pre-forest types in a synoptic way and performing a system of nomenclature in agreement with the international standards initiatives. In this way, the characterization of forest types at community level is related to the environmental planning for the protection of biodiversity
Keywords: Ecological stratiﬁcation; Forest biodiversity; Forest community; forest type; Hierarchical system; Stand-management unit